Establishing early warning systems by monitoring COVID-19 (SARS-CoV-2) in wastewater: COVID-19 in wastewater - Dağlıoğlu, Nebile; Yavuz Güzel, Evşen; Atasoy, Aslı (The Bulletin of Legal Medicine, 2020)
Wastewater based epidemiology studies are a complementary approach used to measure and monitor the presence and prevalence of infectious diseases when clinical testing capacity is limited. It can also help with the detection of coronaviruses in wastewater and how they spread in the society. In the COVID-19 pandemic, SARS-Coronavirus-2 (SARS-CoV-2) is excreted with the feces of infected people and mixed with wastewater. Most people infected with viruses that infect enterically spread their feces and virus into their sewage systems both for the days or weeks before and after symptoms begin to appear. Through the detection of Covid-19 in wastewater, the number of asymptomatic people who do not represent any indication related to diseases but are carriers can be determined, and the total number of people infected in that society can be estimated. Therefore, an early warning system can be created, and it will be possible to take the necessary precautions before the second or third wave occurs.